Peran Kepala Kantor Urusan Agama Dalam Program Bimbingan Perkawinan Di Kantor Urusan Agama Batumarmar Pamekasan - Mustar Mustar; Moh. Jalaludin (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2022)
Research objectives: To describe the role of the head of the Office of Religious Affairs and the implementation of the marriage guidance program at the Batumarmar Pamekasan Religious Affairs Office. Research with a qualitative approach, and phenomenological type. Sources of data in this study were the chairman, staff, and the bride and groom. Data collection techniques used are interviews, observation, and documentation. Data reduction processing techniques, data presentation, and drawing conclusions. Checking the validity of the data by continuous observation, peer checking, as well as triangulation of data sources and triangulation of techniques. The results of the study: (1) the role of the head of the Office of Religious Affairs in marriage guidance (a) dividing tasks, mobilizing, directing, guiding, and coordinating marriage guidance programs to staff members, (b) monitoring and evaluating marriage guidance programs to staff members, and (c) provide services and guidance in the field of marriage, reconciliation and sakinah families, and (2) implementation of marriage guidance programs by providing guidance on the meaning and purpose of marriage, terms and pillars of marriage, rights and obligations of husband and wife, how to resolve family conflicts, and the formation of a sakinah family.